Cellular immune responses in artificially reared pigs - Frank Blecha; D S Pollmann; E F Kluber III (Kansas Agricultural Experiment Station Research Reports, 1984)
An experiment was conducted to determine the influence of artificial rearing on the cellular immune response of young pigs. Artificially reared pigs had lower cellular immune reactivity than sow-reared controls. These results indicate that artificial rearing may result in immunosuppression in young pigs.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Cellular immune responses; Artificially reared